European building construction illustrated - Ching, Francis D. K., 1943-; Mulville, Mark (Hoboken, New Jersey : John Wiley & Sons, 2014)
The first European edition of Francis DK Ching's classic visual guide to the basics of building construction. For nearly four decades, the US publication Building Construction Illustrated has offered an outstanding introduction to the principles of building construction. This new European edition focuses on the construction methods most commonly used in Europe, referring largely to UK Building Regulations overlaid with British and European, while applying Francis DK Ching's clear graphic signature style. It provides a coherent and essential primer, presenting all of the basic concepts.
Concrete Masonry Retaining WallsPad Foundations; Reinforced-Concrete Column; Timber Post; Steel Column; Foundations on Sloping Ground; Concrete Slabs on Grade; Isolation Joints; Construction Joints; Control Joints; Masonry Wall; Stud Wall; Step in Slab Level; Deep Foundations; Pile Foundations -- Driven; Pile Foundations -- Bored; Foundation Choice; 4 FLOOR SYSTEMS; Floor Systems; Concrete; Steel; Timber; Concrete Beams; Concrete Slabs; One-Way Slab; One-Way Ribbed Slab; Two-Way Slab and Beam; Two-Way Waffle Slab; Two-Way Flat Plate; Two-Way Flat Slab; Prestressed Concrete; Pre-tensioning.
"The first European edition of Francis DK Ching's classic visual guide to the basics of building construction."--Provided by publisher.
"Adapted from Francis D.K. Ching. Building Construction Illustrated, Fourth Edition, published by John Wiley & Sons, Inc, Hoboken, New Jersey, copyright 2008"--Title page verso.
Includes bibliographical references and index.
Print version record.
Keywords: Building -- European Union countries; House construction -- European Union countries; Building -- European Union countries -- Pictorial works; House construction -- European Union countries -- Pictorial works; Building -- Estimates -- Europe -- Handbooks, manuals, etc; TECHNOLOGY & ENGINEERING -- Construction -- General; Building; House construction; Europe -- European Union countries; Electronic books; Pictorial works; Electronic books